Lung interstitial cells during alveolarization - Chang Won Choi (Korean Pediatric Society, 2010)
Recent progress in neonatal medicine has enabled survival of many extremely low-birth-weight infants. Prenatal steroids, surfactants, and non-invasive ventilation have helped reduce the incidence of the classical form of bronchopulmonary dysplasia characterized by marked fibrosis and emphysema. However, a new form of bronchopulmonary dysplasia marked by arrest of alveolarization remains a complication in the postnatal course of extremely low-birth-weight infants. To better understand this challenging complication, detailed alveolarization mechanisms should be delineated. Proper alveolarization involves the temporal and spatial coordination of a number of cells, mediators, and genes. Cross-talk between the mesenchyme and the epithelium through soluble and diffusible factors are key processes of alveolarization. Lung interstitial cells derived from the mesenchyme play a crucial role in alveolarization. Peak alveolar formation coincides with intense lung interstitial cell proliferation. Myofibroblasts are essential for secondary septation, a critical process of alveolarization, and localize to the front lines of alveologenesis. The differentiation and migration of myofibroblasts are strictly controlled by various mediators and genes. Disruption of this finely controlled mechanism leads to abnormal alveolarization. Since arrest in alveolarization is a hallmark of a new form of bronchopulmonary dysplasia, knowledge regarding the role of lung interstitial cells during alveolarization and their control mechanism will enable us to find more specific therapeutic strategies for bronchopulmonary dysplasia. In this review, the role of lung interstitial cells during alveolarization and control mechanisms of their differentiation and migration will be discussed.